A cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material for hydrogen production by water electrolysis and a preparation method thereof

By introducing crosslinked structures and multication side chains into the polyarylether anion exchange membrane, the instability of the existing membrane in high temperature and alkaline environments is solved, the alkali resistance stability and ion conductivity of the membrane are improved, and it is suitable for hydrogen production in alkaline water electrolytic cells.

CN117247543BActive Publication Date: 2025-03-04CHANGZHOU UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310856864.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-03-04
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

The existing polyarylether anion exchange membranes have problems such as dimensional instability, low ion conductivity and poor alkali resistance in high temperature and alkaline environments.

Method used

By introducing crosslinked structures to form an ion network structure, the OH-attack on the polymer structure is limited, the alkali resistance stability of the membrane is improved, and the multication side chain is introduced in the uncrosslinked part to improve ion conductivity.

Benefits of technology

It has achieved the improvement of alkali resistance and ion conductivity of the anion exchange membrane, ensured the dimensional stability and chemical stability of the membrane, and is suitable for ion exchange membrane materials for hydrogen production in alkaline water electrolytic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000008764780000011
    Figure FHA0000008764780000011
  • Figure FHA0000008764780000021
    Figure FHA0000008764780000021
  • Figure FHA0000008764780000031
    Figure FHA0000008764780000031
Patent Text Reader

Abstract

The present invention belongs to the field of high-performance anion exchange membranes for hydrogen production by electrolysis of water and their preparation, and specifically discloses a type of cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material and its preparation method and application. By introducing multiple cationic side chains into the polymer structural unit, the aggregation of ions is increased, and by introducing a cross-linked structure to limit the chain spacing, the local OH in the membrane is reduced. ‑ Secondly, the flexible side chain of the benzene ring is used as the spacer between ions to reduce the charge induction effect between ions and the skeleton structure, effectively improving the ion conductivity and chemical stability of the membrane material. The prepared anion exchange membrane can be used in hydrogen production by water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-performance anion exchange membranes for producing hydrogen by electrolysis of water and preparation thereof, and particularly relates to a cross-linked quaternary ammonium functionalized anion exchange membrane material and a preparation method and application thereof. Background Art

[0002] Hydrogen energy has the advantages of high energy density, non-toxic, tasteless, non-corrosive, safe and stable, easy to store and transport, and also has the characteristics of zero carbon emissions and high combustion value. In addition, hydrogen energy can easily realize hydrogen-electricity conversion in fuel cells, and green hydrogen production can also absorb the intermittent and fluctuating shortcomings of solar and wind power generation. At present, the methods of hydrogen production are divided into chemical raw material hydrogen production, hydrogen recovery from hydrogen-containing tail gas byproducts, high temperature decomposition hydrogen production, and water electrolysis hydrogen production, among which water electrolysis hydrogen production is the most environmentally friendly hydrogen production technology. The alkaline anion exchange membrane electrolysis technology has a very broad prospect. It can rely on non-precious metals such as nickel-based as catalysts, and can also carry a higher current density. It has the advantages of low cost, high efficiency and good flexibility. The development of anion exchange membrane water electrolysis technology can effectively avoid the shortcomings of high pollution of alkaline water electrolysis, high cost of proton exchange membrane water electrolysis, and difficulty in the production of solid oxide water electrolysis.

[0003] Anion exchange membrane is one of the most critical components in anion exchange membrane water electrolysis technology, and its performance often determines the performance of the entire water electrolysis system. At present, the dimensional stability, ion conductivity and alkali stability of polyarylether anion exchange membranes with advantages such as strong designability and mature and simple synthesis technology are still a problem to be solved. CN116376019A proposes a type of polyarylether sulfone anion exchange membrane material with sixteen quaternary ammonium cations in the side chain. The dense accumulation of ions improves the ion conductivity. However, the high dense accumulation of quaternary ammonium cations brings great challenges to dimensional stability and alkali stability. When the IEC of the anion exchange membrane reaches 2.51mmol / g, the water absorption rate, swelling rate and ion conductivity at 80℃ are 63.2%, 18.6% and 140.85mS / cm respectively. The ion conductivity retention rate after soaking in 2mol / LNaOH solution at 80℃ for 480h is 72.5%.

[0004] The present invention aims to prepare a cross-linked anion exchange membrane material containing dense quaternary ammonium cations in the side chains by aromatic nucleophilic polycondensation, free radical substitution and Menshutkin reaction. In this work, a cross-linked structure is introduced to form an ion network structure to limit OH -Attack on the polymer structure to improve the alkali stability of the membrane. At the same time, in order to make up for the shortcomings of poor cation activity caused by cross-linking, this work also introduced long side chains of multi-cationic structures, which increased the flexibility of some cations while increasing the cation density, thereby improving ion conductivity. Summary of the invention

[0005] The present invention provides a cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material, which has a structure of formula 1; in formula 1, the number of functionalized structural units is 0.25, and each unit structure contains cross-linked parts in different proportions, m% (molar ratio) = 40% to 100%; the non-cross-linked part (i.e., the polycationic side chain part), (1-m)% = 0% to 60%, the number of non-functionalized structural units is 0.75, and the molecular weight is generally = 50 to 80. The value of m needs to take into account both high ion conductivity and dimensional stability. When m < 40, the instability of the exchange membrane size and ion exchange performance will be caused by water absorption and swelling.

[0006]

[0007] The present invention also provides a method for preparing the cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material as described above, comprising: reacting the polyarylethersulfone containing multiple benzyl bromide structures shown in Formula 2 with self-made 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide and N,N,N',N'-tetramethyl-1,6-hexanediamine shown in Formula 3 to obtain the cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material shown in Formula 1.

[0008]

[0009] The specific preparation method is as follows: first, methyl iodide is added dropwise to N,N,N',N'-tetramethyl-1,6-hexanediamine. Preferably, the reaction temperature of the above reaction is 40-80° C., and the reaction time is 4-6 hours.

[0010] Preferably, the organic solvent is tetrahydrofuran, and its usage is 5 to 10 times the mass of N,N,N',N'-tetramethyl-1,6-hexanediamine.

[0011] Preferably, the amount of N,N,N',N'-tetramethyl-1,6-hexanediamine used is 5 to 10 times that of methyl iodide.

[0012] Secondly, under nitrogen protection, a certain amount of poly(arylethersulfone) polymer containing eight benzyl bromide structures shown in formula 2 is dissolved in an organic solvent, 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide is added first, and N,N,N',N'-tetramethyl-1,6-hexanediamine is added after a period of reaction. After stirring for a period of time, the reactant is filtered and poured into a mold, and after drying, a cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material shown in formula 1 is obtained.

[0013] Preferably, the reaction temperature of the first stage of the above reaction is 50-80°C, and the reaction time is 10-16 hours. The reaction temperature of the second stage is room temperature, and the reaction time is 10-30 minutes. The drying temperature is 50-80°C, and the drying time is 12-48 hours.

[0014] Preferably, the organic solvent is N-methylpyrrolidone or dimethyl sulfoxide, and the amount thereof is 20 to 60 times the mass of the polyarylethersulfone polymer containing the octabenzyl bromide structure.

[0015] Preferably, the amount of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide used is 0 to 0.6 times the molar amount of benzyl bromide in the polyarylethersulfone polymer containing eight benzyl bromide structures.

[0016] Preferably, the amount of N,N,N',N'-tetramethyl-1,6-hexanediamine used is 0.4 to 1 times the molar amount of benzyl bromide in the polyarylethersulfone polymer containing eight benzyl bromide structures.

[0017] Preferably, the polyarylethersulfone polymer containing eight benzylbromide structures is prepared according to the following steps: brominating the polyarylethersulfone containing eight methyl structures shown in formula 4 to obtain the polyarylethersulfone polymer containing multiple benzylbromide structures shown in formula 2.

[0018]

[0019] The specific preparation method is as follows: under nitrogen protection, a certain amount of polyarylethersulfone containing eight methyl structures as shown in formula 4 is dissolved in an organic solvent, benzoyl peroxide and N-bromosuccinimide are added, and the reaction is carried out at 60 to 85° C. for 6 to 8 hours, and the reactant is precipitated in hot ethanol to obtain a polyarylethersulfone polymer containing multiple benzyl bromide structures as shown in formula 2.

[0020] Further preferably, the organic solvent is 1,1,2,2-tetrachloroethane, and the amount used is 30 to 80 times the mass of the polyarylethersulfone polymer containing eight methyl structures; the amount of N-bromosuccinimide used is 2 to 3.5 times (further preferably 2 to 3 times) the molar amount of methyl groups in the polyarylethersulfone polymer containing eight methyl structures; the amount of benzoyl peroxide used is 5% to 9% of the molar amount of N-bromosuccinimide.

[0021] Preferably, the polyarylethersulfone containing eight methyl structures is prepared by the following method: 3,3',5,5'-tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenylsulfone, 4,4'-difluorodiphenylsulfone and 2,2-bis-(4-hydroxyphenyl)hexafluoropropane shown in Formula 5 are subjected to nucleophilic polycondensation reaction.

[0022]

[0023] The specific preparation method is as follows: under nitrogen protection, x parts of 3,3',5,5'-tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenyl sulfone shown in formula 5, 1-x parts of 4,4'-difluorodiphenyl sulfone and 1 part of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane are added into a three-necked flask, and a proper amount of catalyst, organic solvent and dehydrating agent are added to carry out nucleophilic polycondensation reaction, and the reaction is carried out at 130-150° C. for 1-2 hours, followed by dehydration, and then the reaction is carried out at 170-180° C. for 4-8 hours to obtain the polyarylethersulfone containing eight methyl structures shown in formula 3.

[0024] Further preferably, the organic solvent is N-methylpyrrolidone, and its usage is 2 to 7 times the total mass of the three reaction monomers; the catalyst is potassium carbonate; its usage is 2 to 3 times the molar amount of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane; the dehydrating agent is toluene, and its usage is 0.3 to 0.5 times the volume of N-methylpyrrolidone.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material provided by the present invention introduces a cross-linked structure into the polymer structural unit and simultaneously introduces a polycationic side chain into the uncross-linked part. On the one hand, the cross-linked structure limits the chain spacing and reduces the local OH in the membrane. - The concentration of the polymer membrane can be increased, thereby improving the membrane's alkali resistance stability. On the other hand, the cross-linked structure limits the mobility of the chain segments and affects the ion conductivity. The polycationic side chain can increase the aggregation of ionic functional groups and improve the ion conductivity of the polymer membrane material; the benzene ring and the flexible alkane chain can be used to separate the hydrophilic cations from the hydrophobic skeleton, further improving the alkali resistance stability and dimensional stability of the polymer membrane material.

[0027] (2) The cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material provided by the present invention is prepared by the Menshutkin reaction and can be directly used to prepare an ion exchange membrane by a tape casting method. The prepared ion exchange membrane has good ion conductivity, dimensional stability and chemical stability and can be used as an ion exchange membrane material in alkaline water electrolyzers for hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1This is a synthetic route for the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material described in Example 1 of the present invention.

[0029] Figure 2 Middle a, Figure 2 Medium b and Figure 3 This is the NMR spectrum of the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material and the intermediate product described in Example 2 of the present invention.

[0030] Figure 4 Infrared spectra of the cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane materials described in Examples 1, 2, 3, and 4 of the present invention.

[0031] Figure 5 This is a graph of the ion conductivity of the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material described in Examples 1, 2, 3, and 4 of the present invention.

[0032] Figure 6 This is a diagram of the alkali resistance stability of the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material described in Example 2 of the present invention.

[0033] Figure 7 This is a water electrolysis cell performance diagram of the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material described in Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with embodiments:

[0035] The preferred embodiments of the present invention will be described in more detail below in conjunction with specific examples.

[0036] The sources of the drugs and reagents described in the examples are as follows:

[0037] N-Methylpyrrolidone (NMP): aladdin, ≥99.5%

[0038] Dimethyl sulfoxide (DMSO): Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.0%

[0039] Potassium carbonate (K2CO3): Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.0%

[0040] 1,1',2,2'-Tetrachloroethane (TCE): Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.0%

[0041] Benzoyl peroxide (BPO): aladdin, 90.0%

[0042] N,N,N',N'-Tetramethyl-1,6-hexanediamine (TMHDA): Anaiji Chemical, ≥98%

[0043] Iodomethane (CH3I): Anaiji Chemical, ≥98%

[0044] N-bromosuccinimide (NBS): Anaiji Chemical, 98%

[0045] 3,3',5,5'-Tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenyl sulfone (8CH3-DFDPS): prepared according to reference (Journal of Membrane Science, 2015, 492, 281-288), 98%

[0046] 4,4'-Difluorodiphenyl sulfone (DFDPS): Great Wall Reagent, 98%

[0047] 2,2-Bis-(4-hydroxyphenyl)hexafluoropropane (BPAF): Anaiji Chemical, 98%

[0048] Toluene: Sinopharm Chemical Reagent Co., Ltd., ≥99.5%.

[0049] Example 1

[0050] A method for preparing a cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material comprises the following steps:

[0051] (1) Preparation of poly(arylethersulfone) containing eight methyl groups

[0052] 1.6772 g (2.50 mmol) 8CH3-DFDPS, 1.9069 g (7.50 mmol) DFDPS, 3.3623 g (10.00 mmol) BPAF, 2.7642 g (20.00 mmol) K2CO3, 15 mL NMP and 5 mL toluene were added into a 100 mL three-necked flask equipped with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2 h, and then N2 was passed through to remove water and toluene. The temperature was then raised to 175°C for 5 h. The reaction solution was poured into ethanol for precipitation to obtain polyarylethersulfone containing eight methyl structures (PAES-M-25) with a yield of 94%.

[0053] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures

[0054] 2.4 g of octamethyl polyethersulfone (PAES-M-25) and 48 mL of TCE were added to a 100 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and stirred until completely dissolved. Subsequently, 3.2626 g (18.3312 mmol) of NBS as a brominating agent and 0.3330 g (1.3748 mmol) of BPO as an initiator were added, and the reaction was carried out at 80°C for 8.5 h. The reaction solution was poured into hot ethanol for precipitation to obtain polyethersulfone (PAES-Br-25) containing eight benzyl bromide structures with a yield of 86%.

[0055] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide

[0056] A mixed solution of 17.2310 g (0.1000 mmol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and 2.8388 g (0.0200 mmol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel, the temperature was adjusted to 60°C, and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuo at 30°C, with a yield of 95%.

[0057] (4) Preparation of cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane materials

[0058] 0.6g of polyarylethersulfone polymer containing polybenzylbromide structure (PAES-Br-25, benzylbromide content of 1.4771mmol) was dissolved in 24mL of DMSO and added to a three-necked flask equipped with a stirrer and N2 inlet and outlet, and then 0.12507g (0.8862mmol) of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide was added to the three-necked flask, and the temperature was raised to 60°C, and then the reaction was continued for 12h. Then the reaction solution was cooled to room temperature, and 0.1018g (0.5908mmol) of TMHDA was added and stirred for ten minutes. Finally, the mixed solution was poured into the prepared mold and vacuum dried at 60°C for 24h to obtain a quaternary ammonium functionalized cross-linked polyarylethersulfone anion exchange membrane (C-PAES-QA-25-40) with a yield of 98%.

[0059] The synthetic route of the above preparation method is as follows Figure 1 shown.

[0060] Example 2

[0061] A method for preparing a cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material, comprising the following steps

[0062] (1) Preparation of poly(arylethersulfone) containing eight methyl groups

[0063] 1.6772 g (2.50 mmol) 8CH3-DFDPS, 1.9069 g (7.50 mmol) DFDPS, 3.3623 g (10.00 mmol) BPAF, 2.7642 g (20.00 mmol) K2CO3, 15 mL NMP and 5 mL toluene were added into a 100 mL three-necked flask equipped with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2 h, and then N2 was passed through to remove water and toluene. The temperature was then raised to 175°C for 5 h. The reaction solution was poured into ethanol for precipitation to obtain polyarylethersulfone containing eight methyl structures (PAES-M-25) with a yield of 94%.

[0064] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures

[0065] 2.4 g of octamethyl polyethersulfone (PAES-M-25) and 48 mL of TCE were added to a 100 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and stirred until completely dissolved. Subsequently, 3.2626 g (18.3312 mmol) of NBS as a brominating agent and 0.3330 g (1.3748 mmol) of BPO as an initiator were added, and the reaction was carried out at 80°C for 8.5 h. The reaction solution was poured into hot ethanol for precipitation to obtain polyethersulfone (PAES-Br-25) containing eight benzyl bromide structures with a yield of 86%.

[0066] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide

[0067] A mixed solution of 17.2310 g (0.1000 mmol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and 2.8388 g (0.0200 mmol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel, the temperature was adjusted to 60°C, and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuo at 30°C, with a yield of 95%.

[0068] (4) Preparation of cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane materials

[0069] 0.6g of polyarylethersulfone polymer (PAES-Br-25) containing polybenzyl bromide structure was dissolved in 24mL of DMSO and added to a three-necked flask equipped with a stirrer and a N2 inlet and outlet, and then 0.1671g (0.5908mmol) of NQA was added to the three-necked flask, and the temperature was raised to 60°C, and then the reaction was continued for 12h. The reaction solution was then cooled to room temperature, and 0.1527g (0.8862mmol) of TMHDA was added and stirred for ten minutes. Finally, the mixed solution was poured into the prepared mold and vacuum dried at 60°C for 24h to obtain a quaternary ammonium functionalized cross-linked polyarylethersulfone anion exchange membrane (C-PAES-QA-25-60) with a yield of 92%.

[0070] Example 3

[0071] A method for preparing a cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material, comprising the following steps

[0072] (1) Preparation of poly(arylethersulfone) containing eight methyl groups

[0073] 1.6772 g (2.50 mmol) 8CH3-DFDPS, 1.9069 g (7.50 mmol) DFDPS, 3.3623 g (10.00 mmol) BPAF, 2.7642 g (20.00 mmol) K2CO3, 15 mL NMP and 5 mL toluene were added into a 100 mL three-necked flask equipped with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2 h, and then N2 was passed through to remove water and toluene. The temperature was then raised to 175°C for 5 h. The reaction solution was poured into ethanol for precipitation to obtain polyarylethersulfone containing eight methyl structures (PAES-M-25) with a yield of 94%.

[0074] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures

[0075] 2.4 g of octamethyl polyethersulfone (PAES-M-25) and 48 mL of TCE were added to a 100 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and stirred until completely dissolved. Subsequently, 3.2626 g (18.3312 mmol) of NBS as a brominating agent and 0.3330 g (1.3748 mmol) of BPO as an initiator were added, and the reaction was carried out at 80°C for 8.5 h. The reaction solution was poured into hot ethanol for precipitation to obtain polyethersulfone (PAES-Br-25) containing eight benzyl bromide structures with a yield of 86%.

[0076] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide

[0077] A mixed solution of 17.2310 g (0.1000 mmol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and 2.8388 g (0.0200 mmol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel, the temperature was adjusted to 60°C, and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuo at 30°C, with a yield of 95%.

[0078] (4) Preparation of cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane materials

[0079] 0.6g of polyarylethersulfone polymer (PAES-Br-25) containing polybenzyl bromide structure was dissolved in 24mL of DMSO and added to a three-necked flask equipped with a stirrer and a N2 inlet and outlet, and then 0.0836g (0.2954mmol) of NQA was added to the three-necked flask, and the temperature was raised to 60°C, and then the reaction was continued for 12h. The reaction solution was then cooled to room temperature, and 0.2036g (1.1817mmol) of TMHDA was added and stirred for ten minutes. Finally, the mixed solution was poured into the prepared mold and vacuum dried at 60°C for 24h to obtain a quaternary ammonium functionalized cross-linked polyarylethersulfone anion exchange membrane (C-PAES-QA-25-80) with a yield of 96%.

[0080] Example 4

[0081] A method for preparing a cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material, comprising the following steps

[0082] (1) Preparation of poly(arylethersulfone) containing eight methyl groups

[0083] 1.6772 g (2.50 mmol) 8CH3-DFDPS, 1.9069 g (7.50 mmol) DFDPS, 3.3623 g (10.00 mmol) BPAF, 2.7642 g (20.00 mmol) K2CO3, 15 mL NMP and 5 mL toluene were added into a 100 mL three-necked flask equipped with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2 h, and then N2 was passed through to remove water and toluene. The temperature was then raised to 175°C for 5 h. The reaction solution was poured into ethanol for precipitation to obtain polyarylethersulfone containing eight methyl structures (PAES-M-25) with a yield of 94%.

[0084] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures

[0085] 2.4 g of octamethyl polyethersulfone (PAES-M-25) and 48 mL of TCE were added to a 100 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and stirred until completely dissolved. Subsequently, 3.2626 g (18.3312 mmol) of NBS as a brominating agent and 0.3330 g (1.3748 mmol) of BPO as an initiator were added, and the reaction was carried out at 80°C for 8.5 h. The reaction solution was poured into hot ethanol for precipitation to obtain polyethersulfone (PAES-Br-25) containing eight benzyl bromide structures with a yield of 86%.

[0086] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide

[0087] A mixed solution of 17.2310 g (0.1000 mmol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and 2.8388 g (0.0200 mmol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel, the temperature was adjusted to 60°C, and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuo at 30°C, with a yield of 95%.

[0088] (4) Preparation of cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane materials

[0089] 0.6 g of polyarylethersulfone polymer (PAES-Br-25) containing polybenzyl bromide structure was dissolved in 24 mL of DMSO and added to a three-necked flask equipped with a stirrer and a N2 inlet and outlet. The reaction solution was cooled to room temperature and 0.2545 g (1.4771 mmol) of TMHDA was added and stirred for ten minutes. Finally, the mixed solution was poured into the prepared mold and vacuum dried at 60°C for 36 hours to obtain a quaternary ammonium functionalized cross-linked polyarylethersulfone anion exchange membrane (C-PAES-QA-25-100) with a yield of 92%.

[0090] The basic properties of the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material obtained in the above examples are shown in Table 1.

[0091] Table 1

[0092]

[0093] In the table: Test conditions: temperature is 80℃,

[0094] IEC Theo is the theoretical value;

[0095] IEC Tit Measured by titration;

[0096] WU% is the mass change of the membrane before and after water absorption;

[0097] SR% is the change in membrane length before and after water absorption;

[0098] λ is the hydration number;

[0099] σ was measured in pure water by an electrochemical workstation;

[0100] Ea is the activation energy.

[0101] As can be seen from Table 1, the IEC of the prepared C-PAES-QA-25-m membrane Theo The theoretically designed values ​​range from 2.03 to 2.48 mmol g -1 ;IEC Tit Measured by molar titration, ranging from 1.92 to 2.41 mmol g -1 The content of quaternary ammonium cations per unit mass increases with the increase of IEC value, that is, the smaller the cross-linking degree, the higher the IEC. The presence of cations can promote the conduction of ions, so the value of ionic conductivity σ increases with the increase of IEC value. At 80°C, the ionic conductivity increases from 53.43 mS cm -1 Increased to 119.42 mS cm -1 The water absorption (WU) and swelling ratio (SR) also increased with the increase of IEC value. At 80℃, WU increased from 30.9% to 56.7%, and SR increased from 6.3% to 12.9%.

[0102] The ionic conductivity of the membrane is one of the key factors for whether the membrane can be used efficiently. In this work, the ionic conductivity of C-PAES-QA-25-m was measured between 20℃ and 80℃ by the four-electrode method. Figure 5 As shown in Figure 2, the ionic conductivity of the membrane increases with increasing temperature. The increase in temperature causes the polymer chain segments to move violently. Figure 5 As can be seen from the figure, as the temperature rises, the chain segment movement becomes more intense, so the conductivity increases with the temperature rise, but the change is not large. Similarly, as the degree of crosslinking increases, the ionic conductivity of C-PAES-QA-25-m fluctuates less and less with temperature, which is mainly due to the fact that the crosslinking structure restricts the chain segment movement. First, the crosslinking structure reduces the concentration of cationic groups in the polymer unit structure, and second, the crosslinking structure restricts the distance between polymer chains, making the space for water molecules in the membrane smaller, and then the OH carried - The number of migrating water molecules will also decrease.

[0103] When AEMs are assembled in a water electrolyzer, strong alkaline hydroxide ions are produced during the electrolysis process. Therefore, alkali resistance is one of the key properties to measure the performance of anion exchange membranes. This test takes C-PAES-QA-25-60 membrane as an example and immerses it in 2 mol L -1 The membrane was immersed in a NaOH solution at 80°C for 480 h. The membrane's alkali resistance stability was evaluated by measuring the IEC and ionic conductivity of the membrane. Figure 6 As shown in the figure, IEC decreases with time, and its retention rate is 87.8% after 480h. The retention rate of ionic conductivity is 84.7% after 480h durability test.

[0104] Figure 7 The voltage durability curve of the battery is shown at 30°C and 2 mol L -1 NaOH solution as electrolyte, 500 mA cm -2 The steady-state polarization curve was recorded for 480 h at a constant current density of . During the entire test, the voltage fluctuated between 1.69 V and 1.74 V. The overall test shows the feasibility of this type of membrane operating under alkaline conditions.

[0105] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Without departing from the scope and technical principles of the described embodiments, many modifications and changes are obvious to those of ordinary skill in the art, and these modifications and changes should also be regarded as the scope of protection of the present invention.

Claims

1. A cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material, characterized in that: The structural formula is: In Formula 1, the number of functionalized structural units is 0.25, and the number of non-functionalized structural units is 0.75; the functionalized structural unit structure contains a cross-linked portion in a molar ratio of m%, m% = 40% to 100%; the molar ratio of the non-cross-linked portion, i.e., the polycationic side chain portion, is (1-m)% = 0 to 60%.

2. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 1, characterized in that: The method comprises the following steps: reacting a polyarylethersulfone containing eight benzyl bromide structures as shown in formula 2 with 6-dimethylamino-N,N,N-trimethylhexane-1-ammonium iodide and N,N,N',N'-tetramethyl-1,6-hexanediamine to obtain a cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material as shown in formula 1; Where x is 0.25 and y is 0.

75.

3. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 2, characterized in that: The method also includes the following steps: under nitrogen protection, firstly pouring a polyarylethersulfone containing eight benzyl bromide structures into a reaction container and dissolving it with an organic solvent, then sequentially adding 6-dimethylamino-N,N,N-trimethylhexane-1-ammonium iodide and N,N,N',N'-tetramethyl-1,6-hexanediamine into the reaction container and stirring to react, filtering after the reaction is completed, and then pouring the polyarylethersulfone into a mold and drying to obtain a cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material as shown in Formula 1.

4. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 3, characterized in that: The organic solvent is dimethyl sulfoxide, and 6-dimethylamino-N,N,N-trimethylhexane-1-ammonium iodide is first added to react at a reaction temperature of 50 to 80° C. for a reaction time of 10 to 16 hours, and then N,N,N',N'-tetramethyl-1,6-hexanediamine is added to react at room temperature for a reaction time of 10 to 30 minutes.

5. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 2, characterized in that: The preparation method of 6-dimethylamino-N,N,N-trimethylhexane-1-ammonium iodide comprises the following steps: adding methyl iodide dropwise to N,N,N',N'-tetramethyl-1,6-hexanediamine, the solvent is tetrahydrofuran, the amount of N,N,N',N'-tetramethyl-1,6-hexanediamine is 5 to 10 times that of methyl iodide, the reaction temperature is 40 to 80° C., the reaction time is 4 to 6 hours, and the reaction formula is as shown in Formula 3.

6. The method for preparing the cross-linked quaternary ammonium functionalized polyarylethersulfone anion exchange membrane material according to claim 2, characterized in that: The amount of 6-dimethylamino-N,N,N-trimethylhexane-1-ammonium iodide used is 0 to 0.6 times the molar amount of benzyl bromide in the polyaryl ether sulfone containing eight benzyl bromide structures, and the amount of N,N,N',N'-tetramethyl-1,6-hexanediamine used is 0.4 to 1 times the molar amount of benzyl bromide in the polyaryl ether sulfone containing eight benzyl bromide structures.

7. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 2, characterized in that: The preparation method of the polyarylethersulfone containing eight benzylbromide structures comprises the following steps: brominating the polyarylethersulfone containing eight methyl structures shown in formula 4 to obtain the polyarylethersulfone containing eight benzylbromide structures shown in formula 2; Where x is 0.25 and y is 0.

75.

8. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 7, characterized in that: The preparation method of the polyarylethersulfone polymer containing eight benzylbromide structures also includes the following steps: dissolving the polyarylethersulfone containing eight methyl structures described in formula 4 in an organic solvent, then adding an initiator and a brominating agent in sequence, pouring into ethanol for sedimentation after the reaction is completed, filtering and drying, and then obtaining the polyarylethersulfone polymer containing eight benzylbromide structures as shown in formula 2.

9. The method for preparing the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 8, characterized in that: The organic solvent used in the preparation of the polyarylethersulfone polymer containing eight benzylbromide structures is 1,1,2,2-tetrachloroethane, and its usage is 30 to 60 times the mass of the polyarylethersulfone with eight methyl structures; the brominating agent is NBS, and its usage is 2.0 to 3.5 of the molar amount of the methyl group; the initiator is BPO, and its usage is 5% to 9% of the molar amount of NBS; the reaction temperature is 60 to 85°C, and the polyarylethersulfone polymer containing eight benzylbromide structures can be obtained.

10. The use of the cross-linked quaternary ammonium functionalized poly(arylethersulfone) anion exchange membrane material according to claim 1, characterized in that: Used in alkaline water electrolyzers to produce hydrogen.

Citation Information

Patent Citations

  • Polyarylether sulphone membrane material containing sixteen flexible quaternary ammonium cation structures as well as preparation method and application of polyarylether sulphone membrane material

    CN116376019A

  • Polyether sulphone containing plurality of quaternary ammonium salt phenyl side group structures and preparation method for polyether sulphone

    CN104861167A

  • Tertiary amine type polyarylether sulfone (ketone) polymer resin and preparation method and anion-exchange membrane thereof

    CN110294845A